Identification and Analysis of the Design Process of Character Education for Students in Islamic Boarding Schools - Indria, Anita; Mulya Hari, Wino; Hafizh, Muhammad (STIT Ahlussunnah Bukittinggi, 2022)
The mus canduang Islamic boarding school uses its vision and mission as guidelines in the learning process. This shows that the vision and mission of this madrasah encompasses the entire character, both the character recommended in religion and the character recommended by the government. School principals and teachers work together to shape students' character through the existing vision and mission both in the learning process and in extracurricular activities, inside school and outside school. In this case, researchers are interested in researching the identification and analysis of the character education design process implemented at the mus canduang Islamic boarding school. This research is field research using descriptive methods. The research results show that for those selected to be responsible for the position they hold, teachers are also responsible for student activities from the start of learning until the learning is completed. For extracurricular activities, the person responsible is the teacher who guides the activity. Implementation is divided into two, namely intracurricular and extracurricular, intracurricular, namely the learning process in class, the teacher will direct students to pay attention to learning, and students are required to be active and creative. Extracurricular activities are activities carried out outside mandatory class hours such as scouts or cults. Teacher evaluation carries out supervision or observation weekly, or once a month. According to the head of the curriculum at the mus canduang Islamic boarding school, the results of character education have improved, both in terms of discipline and in terms of manners.